Apoptosis in the isolated perfused rat heart: Involvement of reperfusion, oxidants and protein synthesis. - Dean, David C. (University of Ottawa (Canada), 1997)
Reperfusion of an ischemic myocardium has been shown to cause increased injury to the post-ischemic myocardium. Studies exploring the mechanisms of ischemia/reperfusion (IR) injury are abundant and have shown that oxidants, as well as accumulation of metabolic byproducts, play major roles in IR. The isolated perfused heart model has been used very successfully in the past, allowing examination of IR, as well as the application of agents to combat IR injury. However, in the last few years there has been increased interest in a newly discovered component of IR. Apoptosis has recently been determined to occur in the post ischemic heart in vivo by this laboratory, as well as others. It remains unknown whether active cell death contributes to the decrease in myocardial performance characteristic of IR, however, the manipulation of apoptosis using various agents has been successfully documented in many different systems, including cardiac myocytes. Therefore, we sought to determine for the first time if: (1) Apoptosis occurs in the isolated buffer perfused heart and (2) If manipulation of apoptosis would protect against IR injury. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.